First Meetings in Analytic Therapy: Poetics and Pragmatics. Issue 2 (4th May 2022) - Mendelsohn, Eric
Abstract : In this paper, first meetings in analytic therapy are considered thematically, experientially and pragmatically. Attention is given to how we think and feel about beginning therapy, and how these first sessions can be structured so as to facilitate the start of a collaborative analytic project. The history of ideas about first meetings is reviewed and the perspectives in this paper are located in this unfolding narrative. The contributions of several psychoanalytic writers whose ideas have influenced my own are considered. The focus throughout is on the hopes and anxieties of both patient and therapist and how these emerge experientially and procedurally in first meetings. The relational traditions introduced in first meetings can structure opportunities for collaborative, transformational work over the course of time. The ideas presented in this paper are illustrated by an extended case example.